MUGURAŞ CONSTANTINESCU, DANIEL DEJICA, TITELA VÎLCEANU (COORD.). O ISTORIE A TRADUCERILOR IN LIMBA ROMANA SECOLUL AL XX-LEA (ITLR) (VOL. I), BUCUREŞTI, EDITURA ACADEMIEI ROMÂNE, 2021, 1440P. - Torres, Marie Helene (Revista de Letras, 2023)
The present review deals with the first volume of the first translation history systematized in the Romanian language in the 20th century, published in 2021 and coordinated by three professors from three different Romanian universities: Muguraş Constantinescu from the University "Ştefan cel Mare" in Suceava, Daniel Dejica from the University of Timisoara, and Titela Vîlceanu from the University of Craiova.